RESTORATION OF NATIONAL VALUES AND CULTURAL DEVELOPMENT IN UZBEKISTAN (British Journal of Global Ecology and Sustainable Development, 2022)
In the article, our country has repeatedly been subjected to the attack of foreign invaders, has fallen under dependence and julm, so the rich spiritual heritage, traditions of our people are doomed to devaluation. Especially in the era of Tsarist colonialism and the Soviet system, our national values and traditions were trampled. Our native language, rich spiritual heritage were devalued, many mosques-madrasas, national schools, historical monuments were destroyed, left unattended. Starting from the day Uzbekistan gained State independence, thoughts are expressed about the restoration and development of our rich spiritual heritage in our country, raising the spirituality of society to the level of Public Policy.